2017
DOI: 10.1007/s12035-017-0395-8
|View full text |Cite
|
Sign up to set email alerts
|

The Role of GluN2A in Cerebral Ischemia: Promoting Neuron Death and Survival in the Early Stage and Thereafter

Abstract: Over-activation of NMDA receptors is a crucial step required for brain damage following a stroke. Although clinical trials for NMDA receptor blockers have failed, the role of GluN2A subunit in cerebral ischemia has been extensively evaluated in recent years. However, the effect of GluN2A on neuron damage induced by cerebral ischemia remains a matter of controversy. The underlying reason may be that GluN2A mediates both pro-death and pro-survival effects. These two effects result from two mutually excluding pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…However, the tyrosine kinases that demonstrated the highest potential in interrupting GluN2A phosphorylation and protecting CA1 neurons from ischemic processes are GluN2A and Cdk5. Sun et al [ 71 ] studied the signaling pathway characteristics of GluN2A and noted that it plays different roles at varying times during cerebral ischemia. For instance, GluN2A encourages neural death in patients at the acute stage of stroke but induces neuronal survival afterwards.…”
Section: Drug Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the tyrosine kinases that demonstrated the highest potential in interrupting GluN2A phosphorylation and protecting CA1 neurons from ischemic processes are GluN2A and Cdk5. Sun et al [ 71 ] studied the signaling pathway characteristics of GluN2A and noted that it plays different roles at varying times during cerebral ischemia. For instance, GluN2A encourages neural death in patients at the acute stage of stroke but induces neuronal survival afterwards.…”
Section: Drug Researchmentioning
confidence: 99%
“…It was also observed that GluN2B phosphorylation enhances cerebral ischemia and worsens ischemic brain injury [ 71 ]. When DAPK1 and Calcium/calmodulin-dependent protein kinases (CAMKII) bind to NMDAR glutamate receptor (GluN2B) near S1303, increased neural death due to ischemia takes place [ 72 ].…”
Section: Drug Researchmentioning
confidence: 99%
“…Among all the tyrosine kinases, cyclin-dependent kinase 5 (Cdk5) plays a key role in GluN2A phosphorylation, and perturbing interactions between Cdk5 and GluN2A abolished GluN2A phosphorylation and protected CA1 pyramidal neurons from ischemic insult (Wang et al, 2003). In view of the GluN2A signaling-pathway characteristics, we consider that GluN2A may play different roles at different times in cerebral ischemia, that is inducing neuronal death in the acute stage and promoting neuronal survival thereafter (Sun et al, 2018).…”
Section: Roles Of Iglurs In Cerebral Ischemiamentioning
confidence: 99%
“…There exist several pathways through which GluN2A activates CREB (Figure ): GluN2A‐ERK‐CREB, GluN2A‐PI3K‐CREB, GluN2A‐calcium/calmodulin‐dependent protein kinase IV (CaMKIV)‐CREB, and GluN2A‐protein kinase A (PKA)‐CREB (Hajjhussein, Suvarna, Gremillion, Chandler, & O'Donnell, ; Sun, Cheng, Hu, & Gao, ). GluN2B may promote CREB signaling via pathways such as GluN2B‐ERK‐CREB (M. J. Kim et al, ; Melgarejo da Rosa et al, ) and GluN2B‐p38‐CREB (Cuadrado & Nebreda, ), and inhibit CREB signaling through pathways such as GluN2B‐SynGAP‐CREB (M. J. Kim et al, ), GluN2B‐protein kinase G (PKG)‐CREB (Hajjhussein et al, ), and GluN2B‐p38‐CREB (Hui et al, ).…”
Section: Differences In the Effects On Typical Downstream Signaling Mmentioning
confidence: 99%
“…It was reported that Tat-NR2B9c showed no effect on CREB signaling(Soriano et al, 2008). This result indicates that proper inhibition of PDZ proteinmediating pro-death signaling may not interfere with pro-survival signaling, such as CREB signaling.There exist several pathways through which GluN2A activates CREB(Figure 2): GluN2A-ERK-CREB, GluN2A-PI3K-CREB, GluN2Acalcium/calmodulin-dependent protein kinase IV (CaMKIV)-CREB, and GluN2A-protein kinase A (PKA)-CREB(Hajjhussein, Suvarna, Gremillion, Chandler, & O'Donnell, 2007;Sun, Cheng, Hu, & Gao, 2017).GluN2B may promote CREB signaling via pathways such as GluN2B-ERK-CREB (M. J Kim et al, 2005;Melgarejo da Rosa et al, 2016). andGluN2B-p38-CREB(Cuadrado & Nebreda, 2010), and inhibit CREB signaling through pathways such as GluN2B-SynGAP-CREB (M. J Kim et al, 2005),.…”
mentioning
confidence: 99%